Redeveloping Peace in Contemporary Islam - Rochmawati, Nikmah (International Journal Ihya' 'Ulum al-Din, 2018)
There has been a long debate when it comes to understanding the meaning of Islam. The proponents of Islam claim Islam as a religion of peace, while on the other hand, who are mostly Westerners, would dissent this claim by addressing jihad as a violent product of Islam. The Westerners certainly fail to grasp the spirit of peace in Islam because very often their argumentations are based on material events instead of philosophical approach. This paper is an effort to shed light the true meaning of Islam by analyzing it from its philosophical aspects. Literal interpretations are specifically used as a method to analyze texts in the Quran and the Hadith to reveal the etymological, epistemological, and ontological meanings of Islam. Additionally, Max L. Stackhouse’s normativity ethical approach is utilized as a framework to analyze the meaning of Islam from its textual and contextual doctrines. Three prominent concepts (true-false, good-bad, and appropriate-inappropriate) of normativity ethical approach are used in particular to reveal the spirit of peace towards the meaning of Islam. The conclusion derived from the etymological and epistemological analyses is that Islam means obedience, subjugation, and submission to God as an effort to seek safety and happiness in the world and the world after. The ontological analysis shows that Islam is a religion of peace in which its two principal teachings are believing in Allah and nurturing unity and friendship among the mankind. Islam is hoped to be comprehended as a religion that is friendly and becomes rahmatan lil alamin. The analysis using Stackhouse’s normativity ethical approach focuses on the term jihad which is mean restraining from wars. When it comes to wars, jihad must be done with the spirit to erase oppression, enforce the freedom of belief, and disseminate the message of peace. Eventually, jihad itself is the manifestation of peace which is truly the spirit of Islam